2015
DOI: 10.1186/s12879-015-0803-5
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of community-acquired pneumonia and diagnostic yields of microbiological methods: a 3-year prospective study in Norway

Abstract: BackgroundDespite recent advances in microbiological techniques, the etiology of community-acquired pneumonia (CAP) is still not well described. We applied polymerase chain reaction (PCR) and conventional methods to describe etiology of CAP in hospitalized adults and evaluated their respective diagnostic yields.Methods267 CAP patients were enrolled consecutively over our 3-year prospective study. Conventional methods (i.e., bacterial cultures, urinary antigen assays, serology) were combined with nasopharyngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
153
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(185 citation statements)
references
References 43 publications
24
153
2
5
Order By: Relevance
“…Studies that met all the reporting criteria set in our risk of bias assessment were considered of low risk of bias. Analysis of these studies showed a proportion of viral infection of 22.6% (95% CI 18.7-26.5%; I 2 =92.6%) [2,3,7,10,12,17,18,22,23,25,28,29,31,35].…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that met all the reporting criteria set in our risk of bias assessment were considered of low risk of bias. Analysis of these studies showed a proportion of viral infection of 22.6% (95% CI 18.7-26.5%; I 2 =92.6%) [2,3,7,10,12,17,18,22,23,25,28,29,31,35].…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…In patients with dual bacterial and viral infection (10 studies), the odds of death were significantly higher compared with patients without dual infection (OR 2. [3] SAITO [32] HOLM [22] JENNINGS [8] HOHENTHAL [21] CHARLES [17] JOHNSTONE [27] DIEDEREN [20] MERMOND [7] SHIBLI [34] JOHANSSON [26] LIEBERMAN [30] HARA [6] CILLÓNIZ [18] CHOI [2] SANGIL [33] YIN [36] VAN GAGELDONK-LAFEBER [5] LUCHSINGER [9] TAKAHASHI [10] WIEMKEN [11] MUSHER [12] VIASUS [35] HUIJSKENS [24] KIM [29] KARHU [28] HOLTER [23] QU [31] DAS [19] JAIN [25] …”
Section: Short-term Mortalitymentioning
confidence: 99%
“…I to norske studier fant man at henholdsvis 2 % og 4 % av samfunnservervede pneumonier som krevde sykehusinnleggelse skyldtes M. pneumoniae (8,9). M. pneumoniae-infeksjon kan i sjeldne tilfeller i tillegg til autoimmun hemolytisk anemi gi nevrologiske komplikasjoner som encefalitt, myelitt, Guillain-Barrés/Miller-Fishers syndrom og kan ha kardiologiske manifestasjoner som perimyokarditt samt hudmanifestasjoner (10,11).…”
Section: Figur 3 Diagnostisk Algoritme For Utredning Av Autoimmun Hemunclassified
“…Recent studies from Europe reported that approximately 30 of pneumonia cases resulted from a pneumococcal infection (2,4). Our previously published multicenter prospective study showed that pneumococcus was detected in 26.2 of all community-onset pneumonia cases, and the estimated incidence of adult pneumococcal pneumonia in Japan was 473 cases per 100,000 person-years (PYs) (1).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae (pneumococcus) is one of the most common causative agents for adult pneumonia (1)(2)(3)(4). Recent studies from Europe reported that approximately 30 of pneumonia cases resulted from a pneumococcal infection (2,4).…”
Section: Introductionmentioning
confidence: 99%